(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
India’s insurance sector is seen to grow at an alarming rate. As more and more companies enter the insurance world, the competitions tend to raise more. Competition in the sector of insurance in India is strong owing to the fact that there always has been new entries. Hence one of the most crucial factor to stay in the market and resist the rising competition is to induce customer satisfaction. Hence, it turns imperative to not only assess but also work towards factors the promote customer involvement in a particular company. The underlying study focuses on the factors that boost the customer participation in the Ajmer Insurance Company. The major aim is to look out for those factors and then rank them accordingly. An important factors is the demographic variables. Hence the profile of the same has been studied.